Functionalized multidimensional biomaterials for bone microenvironment engineering applications: Focus on osteoimmunomodulation - Lv, Bin; Wu, Juntao; Xiong, Yuan; Xie, Xudong; Lin, Ze; Mi, Bobin; Liu, Guohui (Frontiers in Bioengineering and Biotechnology, 2022)
As bone biology develops, it is gradually recognized that bone regeneration is a pathophysiological process that requires the simultaneous participation of multiple systems. With the introduction of osteoimmunology, the interplay between the immune system and the musculoskeletal diseases has been the conceptual framework for a thorough understanding of both systems and the advancement of osteoimmunomodulaty biomaterials. Various therapeutic strategies which include intervention of the surface characteristics or the local delivery systems with the incorporation of bioactive molecules have been applied to create an ideal bone microenvironment for bone tissue regeneration. Our review systematically summarized the current research that is being undertaken in the field of osteoimmunomodulaty bone biomaterials on a case-by-case basis, aiming to inspire more extensive research and promote clinical conversion.